2021
DOI: 10.1001/jamaoto.2021.1728
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk of Suicide Among Patients With Head and Neck Cancer in Rural, Urban, and Metropolitan Areas

Abstract: IMPORTANCEPatients with head and neck cancer (HNC) are known to be at increased risk of suicide compared with the general population, but there has been insufficient research on whether this risk differs based on patients' rural, urban, or metropolitan residence status.OBJECTIVE To evaluate whether the risk of suicide among patients with HNC differs by rural vs urban or metropolitan residence status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 66 publications
(108 reference statements)
1
14
0
Order By: Relevance
“…The present study also adds to the growing literature on suicide risk in HNC. We found that suicide rates in HPV-related and non–HPV-related HNC were higher than those of the general population, which supports findings from other studies that have examined incidence of suicide in HNC . Factors associated with suicide risk in the current study included being male, White, and unmarried and lack of treatment, as previously described .…”
Section: Discussionsupporting
confidence: 91%
“…The present study also adds to the growing literature on suicide risk in HNC. We found that suicide rates in HPV-related and non–HPV-related HNC were higher than those of the general population, which supports findings from other studies that have examined incidence of suicide in HNC . Factors associated with suicide risk in the current study included being male, White, and unmarried and lack of treatment, as previously described .…”
Section: Discussionsupporting
confidence: 91%
“…Scheduled and opportunistic screening by appropriately trained individuals is highly recommended for targeted populations [ 44 ]. In addition, the unknown prognosis of diagnosed oncological disease causes patients’ anxiety, consequently, the suicide mortality rate among patients with head and neck cancer is high–59, 64, and 127 per 100 000 person-years among residents of metropolitan, urban, and rural counties, respectively [ 45 ]. Therefore, a brief psychosocial screening protocol should be implemented in routine ambulatory oncology care as 57% of HNSCC patients were identified with clinical distress [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most suicides occurring in those over the age of 60 years are related to an underlying medical illness [25]. Several groups have established that patients with cancer are at increased risk of suicide [26][27][28][29]. Suicide, however, is just one manifestation of distress.…”
Section: Suicide and Self-harmmentioning
confidence: 99%
“…Body image-related distress is a disorder characterized by a distressing self-perceived change in appearance and function [44,45]. It can lead to social isolation, stigmatization, depression, and self-harm [26,46]. A 24-item disease-specific patient-reported outcome was recently created to assess body image distress among head and neck cancer patients – The Inventory to Measure and Assess Image Disturbance – Head and Neck (IMAGE-HN) [47 ▪▪ ,48].…”
Section: Screening For Emotional Distress Through Patient-reported Ou...mentioning
confidence: 99%